Castleman flare or COPD exacerbation— can biomarkers override availability bias?. (2020) - Claxton, Benjamin B.; Dimmock, Anne E.F.; Jain, Rohit; Drummond, M. Bradley; Bascom, Rebecca
Abstract: Effective treatments for human herpes virus 8 (HHV-8) associated multicentric Castleman disease (MCD) have led to prolonged survival for this complex systemic lymphoproliferative inflammatory disease. Nonetheless, significant challenges remain for the recognition of disease exacerbations, particularly when overlapping with common comorbid conditions. We present a case of a 60-year-old man with a 22-year history of MCD, current advanced COPD, and medication-controlled HIV. His recurrent presentations with flares of fatigue, worsening dyspnea, and productive cough were confusing to clinicians who were attempting to distinguish between exacerbations of MCD or COPD. Published biomarkers of MCD flare include HHV-8 and CRP, which were proposed by the patient to his clinicians as useful in guiding treatment. This case illustrates the value of patient insight as an antidote to the problem of availability bias. Highlights: Pathophysiology and presentation of Castleman disease are reviewed. HHV-8 viral load and CRP are valuable in identifying Castleman flares. There is increased risk of availability bias in patients with multiple comorbidities. Shared decision making remains paramount, especially in patients with rare diseases.